2022
DOI: 10.1038/s41598-022-26315-7
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes, spectacle independence, and patient satisfaction of pseudophakic mini-monovision using a new monofocal intraocular lens

Abstract: Modified monovision—or “mini-monovision”—is an alternative method to multifocal intraocular lenses (IOLs) for treating presbyopia. This study aimed to evaluate the clinical outcomes of patients bilaterally implanted with the new enhanced monofocal Tecnis Eyhance (ICB00) IOLs with the mini-monovision technique to improve near vision. In this retrospective case series, the medical records of 50 patients (100 eyes) who underwent bilateral cataract surgery were reviewed. Patients were divided into the Emmetropia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… 33 In a comparison of 25 patients in each group, the authors found minimal and non-significant differences in bilateral UDVA and UIVA (0.03 logMAR difference), but almost 2 Snellen lines better UNVA with the mini-monovision approach. 33 This is different from our findings, likely because patients in the previous study had a more myopic spherical equivalent, even in the bilateral emmetropia group (mean MSE: bilateral emmetropia group: −0.18 ± 0.21 D vs mini-monovision group: dominant eye −0.19 ± 0.18 D, non-dominant eye: −0.95 ± 0.19 D), 21 while MSE was closer to plano in eyes targeted for emmetropia in our study. However, their patient-reported findings agree with our conclusions that there was no difference in visual phenomena and overall patient satisfaction between bilateral emmetropes and those with mini-monovision.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“… 33 In a comparison of 25 patients in each group, the authors found minimal and non-significant differences in bilateral UDVA and UIVA (0.03 logMAR difference), but almost 2 Snellen lines better UNVA with the mini-monovision approach. 33 This is different from our findings, likely because patients in the previous study had a more myopic spherical equivalent, even in the bilateral emmetropia group (mean MSE: bilateral emmetropia group: −0.18 ± 0.21 D vs mini-monovision group: dominant eye −0.19 ± 0.18 D, non-dominant eye: −0.95 ± 0.19 D), 21 while MSE was closer to plano in eyes targeted for emmetropia in our study. However, their patient-reported findings agree with our conclusions that there was no difference in visual phenomena and overall patient satisfaction between bilateral emmetropes and those with mini-monovision.…”
Section: Discussionmentioning
confidence: 92%
“…The satisfaction and visual phenomena were, however, comparable between bilateral emmetropes and those with mini-monovision. There are two studies that discuss mini-monovision aim with Tecnis Eyhance IOL; 15 , 33 one of them has a similar design comparing bilateral emmetropes to mini-monovision patients of the study IOL. 33 In a comparison of 25 patients in each group, the authors found minimal and non-significant differences in bilateral UDVA and UIVA (0.03 logMAR difference), but almost 2 Snellen lines better UNVA with the mini-monovision approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased spectacle independence has resulted in an increase in quality of life after surgery and increased patient satisfaction. [1][2][3][4] Monofocal IOLs are commonly implanted and provide good distance vision and minimal visual disturbances; however, monofocal IOLs are not designed to offer spectacle independence at near or intermediate. On the other hand, multifocal IOLs have been shown to provide acceptable visual acuity from distance to near; however, their main disadvantages remain a loss in contrast sensitivity and increased visual disturbances such as halos and glare.…”
mentioning
confidence: 99%